Exploring the physiological roles of circular RNAs in livestock animals. (20th December 2022) - Raza, Sayed Haidar Abbas; Wijayanti, Dwi; Pant, Sameer D.; Abdelnour, Sameh A.; Hashem, Nesrein M.; Amin, Ahmed; Wani, Atif Khurshid; Prakash, Ajit; Dawood, Mahmoud A.O.; Zan, Linsen
Abstract: Circular RNAs (circRNAs) are a recently identified class of RNAs produced via back-splicing and covalent linkage between RNA ends, resulting in a circularized RNA molecule. Physiologically, circRNAs are known to influence a variety of biological pathways, and can also regulate transcription, post-transcription, RNA splicing, or interaction with other proteins or microRNAs (miRNAs). Functionally, circRNAs are known to competitively bind to various other RNA molecules including miRNAs and other competing endogenous RNA such as long noncoding RNA, thereby significantly influencing gene expression. Since gene expression is a crucial factor that underlies economically important livestock traits, it is likely that circRNAs significantly influence livestock traits like growth, milk production, reproduction, meat quality, hair follicle growth, and gametogenesis. Thousands of circRNAs have been recognized in different species of animals, and some of these circRNAs have also been shown to regulate stress responses that may be crucial for animal welfare. Therefore, in this review, we aim to highlight the biogenesis of circRNAs, along with its potential implications for livestock. The presented summary would offer a fundamental understanding of the molecular machinery that underlies circRNAs and associated biological phenomena and emphasize the need for further explorations into the role of circRNAs in the other productive, reproductive, and physiological attributes in animals. Highlights: CircRNAs are a class of RNA molecules that are attracting increasing interest because they have been found to interact with a variety of proteins or miRNAs and influence multiple biological pathways. Significant evidence is emerging in support of circRNAs contributing to a range of physiologies in livestock. This review summarizes CircRNA characteristics, and key biological functions of circRNAs, specifically in the context of livestock.